2011
DOI: 10.1007/s10201-011-0357-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, ecological tolerance and optimum levels of freshwater Ostracoda (Crustacea) from Diyarbakır, Turkey

Abstract: A total of 23 ostracod taxa were found in 48 of 90 different water bodies (wetlands, springs, lakes, creeks, etc.) located at moderate to high elevation (530-1,095 m) in Diyarbakır province. The ecological tolerances and optimum values for environmental variables of 15 species were analyzed. Accordingly, maximum numbers of species were found between 700 and 800 m. Ostracod species and sampling sites along with seven environmental variables were ordinated with canonical correspondence analysis (CCA). The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…As shown in Table 3, especially cosmopolitan species (e.g., H. incongruens, C. neglecta, I. bradyi, P. olivaceus, H. salina) have high tolerance levels when we compared with others. Having high tolerance levels allow them to adapt unsteady environment and contribute to their wide ranges for different variables (e.g., pH, dissolved oxygen, conductivity) they tolerate (Külköylüoğlu et al 2012a). For example, P. olivaceus and C. ophtalmica had highest (6.34) and lowest (0.65) tolerance levels for water temperature and their ranges (optimum ± tolerance levels) are like that 9.16-21.84 and 17.21-18.51°C, respectively (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3, especially cosmopolitan species (e.g., H. incongruens, C. neglecta, I. bradyi, P. olivaceus, H. salina) have high tolerance levels when we compared with others. Having high tolerance levels allow them to adapt unsteady environment and contribute to their wide ranges for different variables (e.g., pH, dissolved oxygen, conductivity) they tolerate (Külköylüoğlu et al 2012a). For example, P. olivaceus and C. ophtalmica had highest (6.34) and lowest (0.65) tolerance levels for water temperature and their ranges (optimum ± tolerance levels) are like that 9.16-21.84 and 17.21-18.51°C, respectively (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of elevation is a longterm debate in the literature. Some studies stated that elevation was a limiting factor for ostracods (e.g., Mezquıta et al 1999, Pıerı et al 2009, zooplankton (Shehu et al 2009) and avian species (Şekercİoğlu et al 2008) but others (e.g., Laprıda et al 2006, Külköylüoğlu et al 2012a, Guo et al 2013, Yavuzatmaca et al 2015 did not support this idea. The elevational limitation of vectors (e.g., birds) that contributes to the dispersion of ostracods to long distance may allow to any one say that elevation is a secondary factor (Martınez-Garcıa et al 2015, Yavuzatmaca et al 2015 limits the passive distribution of ostracods.…”
Section: Introductionmentioning
confidence: 99%
“…During the present study, the species showed minimum tolerance value for pH and optimum value for Tw and salinity while maximum optimum value was calculated for SHE. Külköylüoğlu, Akdemir, and Yüce (2011) estimated a high tolerance of the species to salinity while Külköylüoğlu and Sarı (2012) displayed a positive correlation to SHE value. Our results suggest that both species have relatively low tolerance (under the mean tolerance value) values for some variables (Sal, Ca +2 , Cl −1 , Tw) in the shallow waters of Malatya.…”
Section: Discussionmentioning
confidence: 99%
“…At the regional scale, the observed variation is partly organised along altitude, latitude, and water temperature. Van der Meeren et al (2010), Stoch et al (2011), andKülköylüo! glu et al (2012a) stressed the importance of altitude for ostracod community composition.…”
Section: Discussionmentioning
confidence: 99%